Potency of Black Soybean (Glycine max L. Merr) and Jati Belanda Leaves (Guazuma ulmifolia Lamk) for Dyslipidemia Treatment In Vivo - Sijani Prahastuti; Meilinah Hidayat; Michael W. Kurniadi; Selvina Christiany (Journal of Medicine and Health, 2016)
Soybean Detam 1 and Jati Belanda leaves are potential alternative medicines for treating dyslipidemia. The purpose of this study is to explore the potential of the combination of Ethanolic Extract Soybean Detam 1 (EEKD) and Jati Belanda (EEJB) in lowering LDL cholesterol and triglycerides compared to single extract and Simvastatin. Using a real laboratory experimental method with CRD, a total of 36 male Wistar rats were divided into 6 groups and administrated for treatment of 28 days. The results showed a significant decrease of LDL cholesterol as well as triglyceride in NC as compared to P1, P2, P3 (p <0.05) and no significant difference with PC (p> 0.05). The highest suppression of LDL cholesterol between P1 with P2 and P3 is (p <0.05) while the triglyceride is between P1 and P2 (p <0.05). This study concludes that the combination of EEKD 10 mg, 20 mg EEJB, EEKD 30 mg and EEJB 30 mg is significantly lowering LDL cholesterol and triglyceride. The combination of EEKD 10 mg, 20 mg EEJB is the highest compression of LDL cholesterol and triglyceride, and has an equivalent effect with simvastatin in lowering LDL cholesterol and triglycerides in male Wistar rats induced with high fat diet. Keywords: LDL cholesterol, triglycerides